2012
DOI: 10.1001/archophthalmol.2012.2391
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Pars Plana Vitrectomy in Eyes With Plaque-Irradiated Posterior Uveal Melanoma

Abstract: Management of vitreous hemorrhage by PPV in eyes with previously irradiated uveal melanoma appears to be safe and without increased risk for intraocular, local, orbital, or systemic dissemination of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…This is consistent with previously published rates of 1.2% (47 from 3841 eyes) reported by Bansal et al 8 and 2.0% (74 of 3707 eyes) by Bianciotto et al, 9 both following application of Iodine-125 plaques. In keeping with our findings, existing literature recognises that vitrectomy for vitreous haemorrhage following plaque brachytherapy is usually a late phenomenon 8,10 and commonly associated with radiation retinopathy. 9 We had no cases of vitrectomy for vitreous haemorrhage following primary PBT, although Tran et al 7 report a rate of 2.0% after an average of 21 months, and with vitreous haemorrhage more common with more posteriorly located tumours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previously published rates of 1.2% (47 from 3841 eyes) reported by Bansal et al 8 and 2.0% (74 of 3707 eyes) by Bianciotto et al, 9 both following application of Iodine-125 plaques. In keeping with our findings, existing literature recognises that vitrectomy for vitreous haemorrhage following plaque brachytherapy is usually a late phenomenon 8,10 and commonly associated with radiation retinopathy. 9 We had no cases of vitrectomy for vitreous haemorrhage following primary PBT, although Tran et al 7 report a rate of 2.0% after an average of 21 months, and with vitreous haemorrhage more common with more posteriorly located tumours.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies report successful vitrectomy for clearance of vitreous haemorrhage following Iodine-125 brachytherapy at rates of 53/74 (72%) 9 and 35/47 (74%), 8 but the visual outcomes were poor with 34/47 (72%) 8 of eyes achieving an acuity of 6/60 or worse, attributed to radiation retinopathy. In contrast, our rate of complete clearance of vitreous haemorrhage was lower at 2/6 (33%) but with similar final visual acuity of 6/60 or worse in 4/6 (67%).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent report from our data has shown that vitrectomy is safe and effective for eyes with melanoma and vitreous hemorrhage after radiotherapy. 2 Based on their experience with ruthenium plaque radiotherapy for uveal melanoma, Avanish et al have posed a few additional queries. They question the etiology of vitreous hemorrhage in their case of small melanoma that occurred 1 week after transretinal tumor biopsy with vitreous cutter.…”
Section: Replymentioning
confidence: 99%
“…More recently, Bansal et al reported on the author's experience with vitrectomy for vitreous hemorrhage in eyes with posterior choroidal melanoma. [25] They reviewed the medical records of 47 patients who underwent vitrectomy for vitreous hemorrhage following Iodine-125 brachytherapy for posterior choroidal melanoma. The primary outcome of their analysis included rates of intraocular tumor dissemination, extrascleral extension, local tumor recurrence, and systemic metastasis.…”
Section: Pars Plana Vitrectomy For Complications After Brachytherapy mentioning
confidence: 99%
“…In summary, the reports by Foster et al, [24] Bansal et al, [25] and Mason and Mullins [15] reveal the safety of performing vitrectomy in patients who have been treated with brachytherapy for choroidal melanoma. The combined reports by Foster and Mason found zero of 29 patients developed metastatic disease following vitrectomy, while Bansal found only four of 47 patients to have developed metastatic disease following vitrectomy in patients with treated choroidal melanoma.…”
Section: Pars Plana Vitrectomy For Complications After Brachytherapy mentioning
confidence: 99%